2014
DOI: 10.5812/jjm.9450
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genital Chlamydia trachomatis Infection Incidence Between Women With Infertility and Healthy Women in Iran Using PCR and Immunofluorescence Methods

Abstract: Background:For a long time, infertility has been one of the most sequels in medical sciences with microbial agents as one group of its causes. The possible etiological role of Chlamydia trachomatis in infertility was suggested years ago, but it has not yet been proved completely. To decrease the severe involvements of C. trachomatis infections, screening by efficient diagnostic methods are necessary.Objectives:In this study we attempted to determine the incidence of C. trachomatis in infertile women and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 16 publications
1
12
1
1
Order By: Relevance
“…As seen in Fig. 7, ORs for all these studies 26,31,43,47,48 except one 27 were above 1, P-values for three surveys were below 0.05, 31,47,48 the overall OR was 2.3 (95% CI, range: 1.1-4.6), and the overall P-value was 0.02;…”
Section: Discussionmentioning
confidence: 99%
“…As seen in Fig. 7, ORs for all these studies 26,31,43,47,48 except one 27 were above 1, P-values for three surveys were below 0.05, 31,47,48 the overall OR was 2.3 (95% CI, range: 1.1-4.6), and the overall P-value was 0.02;…”
Section: Discussionmentioning
confidence: 99%
“…Mohammed et al (2017) 90 Goshayeshi et al (2015) 58 Sisakht et al (2017) 76 Awwad et al (2003) 95 Bagheri et al (2018) 53 Safdari et al (2015) 74 Zahirnia et al (2018) 78 Mosbah and Nabiel (2016) 43 Mosbah and Nabiel (2016) 43 Nada et al (2015) 45 Mousavi et al (2014) 69 El−Sayed et al (2002) 42 Ahmadi et al (2016a) 48 Joolayi et al (2017) 62 Al-Thani (2013) 110 As'ad (2004) 94 Awad et al (2013) 112 Al-Ramahi et al (2008) 93 Mahafzah et al (2008) 96 Marashi et al (2014) 66 Javanmard et al (2018) 61 Jordan Ministry of Health (2004) 97 Al-Thani (2013) 110 Rashidi et al (2013) 71 Pourabbas et al (2018) 70 Dehghan et al (2017) 57 The Middle East and North Africa HIV/AIDS Epidemiology Synthesis Project (2017) 105 with miscarriage and in pregnant women-similar to that found in pregnant women in lowincome and middle income countries elsewhere. [213][214][215][216][217] This stigmatised and largely asymptomatic infection might not be visible to the public eye, but its reproductive health sequelae are visible, even if not explicitly linked to the underlying cause.…”
Section: Womenmentioning
confidence: 99%
“…Medical Education (2008) 67 Gdoura et al (2008) 178 Sadrpour et al (2013) 164 Al-Sweih et al (2012) 100 Ahmadi et al (2018) 49 Golshani et al (2007) 155 Dehghan et al (2017) 57 Moazenchi et al 2018159 Total Random effects model Heterogeneity: 93 Al-Ramahi et al (2008) 93 Joolayi et al (2017) 62 Al-Ramahi et al (2008) 93 Rashidi et al (2013) 71 Ahmed (2012) 167 Abdella et al (2015) 144 Hajikhani et al (2013) 156 Al-Ramahi et al (2008) 93 Joolayi et al (2017) 62 Mohammed et al (2017) 90 Siam and Hefzy (2012) 151 Kalantar et al (2007) 157 Gdoura et al (2001b) 177 Alfarraj et al (2015) 174 Dawood (2011) 169 Elkayal et al (2015) 146 Goshayeshi et al (2015) 58 Nada et al (2015) 45 Mousavi et al (2014) 69 Mansour Ghanaie (2014) 158 Marashi et al (2014) 66 Rashidi et al (2013) 71 Dehghan et al (2017) 57…”
Section: Prevalence (95% Ci)mentioning
confidence: 99%
“…5 - 9 The association between C. trachomatis infection and infertility has been the subject of several research. A study in Iran 10 suggested the significant association between C. trachomatis infection and female infertility with a prevalence rate of 15.3%. The same finding was suggested by a study conducted in India, which confirmed the significant association between infertility and the duration of C. trachomatis infection.…”
mentioning
confidence: 99%